ANALISIS ANGKUTAN SEDIMEN MENGGUNAKAN METODE EMPIRIS DAN PEMODELAN NUMERIS PADA SALURAN DRANASE DI KELURAHAN SUMBER JAYA KOTA BENGKULU - Rizki Akbar; Khairul Amri; Rena Misliniyati; Lindung Zalbuin Mase; Hardiansyah (Wahana Teknik Sipil: Jurnal Pengembangan Teknik Sipil, 2026)
Sedimentation in drainage channels can reduce flow capacity and cause flooding. This study aims to analyze sediment characteristics, sediment transport capacity, and its impact on drainage channels in Sumber Jaya Village, Bengkulu City. Sediment samples were taken from five points 100 meters apart, then tested in the laboratory to determine their physical properties and analyzed using empirical and numerical methods, namely Meyer-Peter Müller, Ackers - White, and DuBoys. The test results showed that the sediment was dominated by poorly graded sand with silt or clay content. The average sediment transport capacity obtained was 150.6398 tons/year using the empirical Meyer-Peter Müller method, 153.9395 tons/year using the numerical modeling of Meyer-Peter Müller, 188.409 tons/year using the DuBoys method, and 57.816 tons/year using the Ackers - White method. The average sedimentation percentage of drainage channels reached 12.38% and was classified as a sufficient channel. The results of this study confirm that sedimentation has a significant effect on drainage capacity, requiring rehabilitation measures and further study. These findings are expected to form the basis for sediment management and sustainable drainage infrastructure planning in urban areas.